Uji Aktivitas Antioksidan dan Profil Fitokimia Ekstrak Kayu Beta-beta (Lunasia amara Blanco.): Antioxidant Activity and Phytochemical Profile of Beta-beta (Lunasia amara Blanco) Wood Extract - Hasnaeni, Hasnaeni; Aminah, Aminah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
Beta-beta wood (Lunasia amara Blanco) is one of the Rutaceae plants. It has been used traditionally in Indonesia, both in the form of a single extract or in a mixture of several herbs, for the treatment of swollen feet, skin diseases and inflammation or irritation of the eyes. This study aims to examine the antioxidant activity and the phytochemical profile of beta-beta wood extract. The research methods include plant extraction by maceration, testing of antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and phytochemical profiling with specific chemical reagents. The results showed that beta-beta wood extract (Lunasia amara Blanco) has antioxidant activity with IC50 was 69.46 Î¼g/ml (0.069 mg/ml) and it contained steroid, phenolic, saponin, alkaloid and coumarin compounds.